Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: Organic Disease or Psychosomatic Illness? A Re-Examination of the Royal Free Epidemic of 1955 - Rosemary Underhill; Rosemarie Baillod (Medicina, 2020)
Background and Objectives: Controversy exists over whether myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is an organic disease or a psychosomatic illness. ME/CFS usually occurs as sporadic cases, but epidemics (outbreaks) have occurred worldwide. Myalgic encephalomyelitis was named to describe an outbreak affecting the lymphatic, muscular, and nervous systems that closed the Royal Free hospital for three months in 1955. Fifteen years later, two psychiatrists concluded that epidemic hysteria was the likely cause. ME/CFS research studies show multiple pathophysiological differences between patients and controls and a possible etiological role for infectious organisms, but the belief that ME/CFS is psychosomatic is widespread and has been specifically supported by the epidemic hysteria hypothesis for the Royal Free outbreak. Our objective was to obtain accounts from ex-Royal Free hospital staff who personally experienced the 1955 outbreak and evaluate evidence for it being an infectious illness versus epidemic hysteria. Materials and Methods: Statements in the newsletters of two organizations for staff who had worked at the Royal Free hospital invited anyone who had experienced the 1955 Royal Free outbreak to contact the authors. Accounts of the outbreak from telephone interviews and letters were evaluated against the “epidemic hysteria hypothesis” paper and original medical staff reports. Results: Twenty-seven ex-Royal Free hospital staff, including six who had developed ME, provided descriptions typical of an infectious illness affecting the lymphatic, muscular, and nervous systems, and were not consistent with epidemic hysteria. Conclusions: The 1955 Royal Free hospital epidemic of myalgic encephalomyelitis was an organic infectious disease, not psychogenic epidemic hysteria.